Pengembangan Arsitektur Data Sistem Informasi Pondok Pesantren - Istiqomah, Nanda Ayu; Imayah, Khoirotul; Saidah, Nuris; Yaqin, Muhammad Ainul (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2020)
Data management is very necessary in an institution to facilitate data processing. One of them is Islamic education institutions or Islamic boarding schools that have developed nformation systems for Islamic boarding school. In building a boarding school information system, applications and data are needed. Data architecture obtained from a hierarchy of information systems consisting of executive information systems, management informations systems, and transaction processing systems. Architecture design of information systems for Islamic boarding school is done by building an ERD (Entity Relationship Diagram) from a collection of data needed on boarding school information systems. ERD is a database building model by describing relations between database entities.